Natural convection in a triangle enclosure with flush mounted heater on the wall - Varol, Yasin; Koca, Ahmet; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2006)
Natural convection heat transfer has been analyzed numerically in a triangle enclosure with flush mounted heater on vertical wall. Finite difference method is used in solution of governing equations in streamfunction-vorticity form and linear algebraic equations were solved via Successive Under Relaxation (SUR). Governing parameters on heat transfer and flow fields are aspect ratio of triangle, location of heater, length of heater and Rayleigh number. It is observed that the most important parameter on heat transfer and flow field is the position of heater which can be a control parameter for the present system. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: natural convection; triangular cavity; particularly heated wall